2007
DOI: 10.1002/dc.20736
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell tumor of the breast

Abstract: We report a case of a 43-yr-old woman with a granular cell tumor of the breast. She presented with a palpable mass of the left breast of 2-yr duration. On physical examination, a firm, painless, well-defined mass located at the union of the upper quadrants was observed and a palpable homolateral axillary lymph node. The tumor was dense with ill-defined borders at mammography and hypoechoic, hypovascular, and poorly limited at ultrasonography. Fine needle aspiration cytology of the lesion was performed. Cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 12 publications
1
49
0
Order By: Relevance
“…[17] The fragile granular cytoplasm of GCT can lead to a “dirty” background synonymous with necrosis that can be seen in breast carcinoma and other malignancies. [18] In the cases where GCT shows a degree of cellular and nuclear atypia, apocrine cancer and metastatic lesions such as renal cell carcinoma and melanoma must be ruled out. [16] This is accomplished with immunohistochemical stains such as S-100, vimentin, and CEA.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The fragile granular cytoplasm of GCT can lead to a “dirty” background synonymous with necrosis that can be seen in breast carcinoma and other malignancies. [18] In the cases where GCT shows a degree of cellular and nuclear atypia, apocrine cancer and metastatic lesions such as renal cell carcinoma and melanoma must be ruled out. [16] This is accomplished with immunohistochemical stains such as S-100, vimentin, and CEA.…”
Section: Discussionmentioning
confidence: 99%
“…2 The GCT of the breast accounts for between 5 and 15% of all GCT cases. It occurs in a wide range of ages from teenagers to elderly, most commonly in women between 30 and 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 Most reports published on the histological features of GCTs have been on lesions from the breast, respiratory tract or digestive tract. [1][2][3]5,6 Few reports have been on the diagnosis of GCTs by fine needle aspiration cytology. 4,5,7,[9][10][11] One report described a case of GCT in the inguinal region that was misdiagnosed by cytology, 4 while another reported that GCT of the breast could be misdiagnosed as breast cancer when using fine needle aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The majority of GCTs are benign, but they are often misdiagnosed, based on clinical and cytological tests and examination of frozen sections. [4][5][6] There have been few reports on the cytopathological examination of GCTs. [7][8][9][10][11] The present case report describes the cytological features of a GCT of the abdominal wall, which was diagnosed by fine needle aspiration cytology and confirmed by histology.…”
Section: Introductionmentioning
confidence: 99%